1987
DOI: 10.1159/000199579
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective and Ulcer Healing Properties of Prostaglandin E<sub>2</sub>, Colloidal Bismuth and Sucralfate in Rats

Abstract: This study describes the model of chronic gastric and duodenal ulcerations induced by the application of acetic acid on a strictly defined area of the serosal surface of the stomach and duodenum for 10 and 20 s, respectively. Acetic acid applied for longer (20–60 s) or on a larger area (28–64 mm2) resulted in the formation of severe ulcerations which penetrated into the surrounding organs and had very prolonged healing time. Ulcers induced by the application of acetic acid for 10–20 s on a smaller a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 12 publications
2
37
0
3
Order By: Relevance
“…dose-dependently inhibited food intake stimulated by ghrelin in rats with GF. At the dose used in the present study, indomethacin has been shown previously to inhibit gastric PGE 2 generation by ϳ90% without itself causing any mucosal damage (Konturek et al, 1987). The doses of SC560 and rofecoxib were selected on the basis of previous studies showing that these agents almost completely suppress PGE 2 generation in exudate of air pouch inflammation and inhibit gastric PGE 2 production in mucosa with preexisting gastric ulcer (Lesch et al, 1998;Brzozowski et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…dose-dependently inhibited food intake stimulated by ghrelin in rats with GF. At the dose used in the present study, indomethacin has been shown previously to inhibit gastric PGE 2 generation by ϳ90% without itself causing any mucosal damage (Konturek et al, 1987). The doses of SC560 and rofecoxib were selected on the basis of previous studies showing that these agents almost completely suppress PGE 2 generation in exudate of air pouch inflammation and inhibit gastric PGE 2 production in mucosa with preexisting gastric ulcer (Lesch et al, 1998;Brzozowski et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…As expected, PG analogs significantly enhanced the spontaneous healing of acetic acid ulcers and prevented a delay in ulcer healing by repeated indomethacin treatment. [93][94][95][96][97] Penney et al 98) demonstrated that misoprostol reversed the delayed healing effect of aspirin via an effect on epithelial regeneration. Arakawa et al 99) examined the effects of rebamipide, a novel PG-inducer, on healing and relapse of acetic acid ulcers in rats.…”
Section: Mucosal Defensive Drugsmentioning
confidence: 99%
“…Since Konturek et al (37) indicated that ulcer healing rate is dependent on its initial size, it is possible that shrinkage of ulcer size causes ulcer healing. In the present study, we found that the length of the ruptured muscularis mucosa in aged animals was significantly less than that in young animals, indicating that aging promotes tissue contraction.…”
Section: Gastric Motilitymentioning
confidence: 99%